Peran Koperasi Dalam Mewujudkan Ekonomi Kerakyatan Guna Meningkatkan Kesejahteraan - Ul Huda, Isra; Fahrin Sapar, Jhony (GEMA EKONOMI, 2023)
This research was conducted at Sumber Sejahtera Credit Union in South Kalimantan. A credit union is a cooperative financial institution owned and controlled by its members. Credit unions are non-profit and provide a safe, comfortable place for members to save money and obtain loans and other services at competitive prices. The purpose of this study is to determine the role of Sumber Sejahtera Credit Union cooperative on the welfare of its members. The type of research used by researchers is qualitative and quantitative and the results of the study describe many questionnaire results and observations. The results of the research obtained the role of the Sumber Sejahtera Credit Union Cooperative have a significant impact on the welfare of the community. The efforts made by cooperatives in achieving their goals, namely the welfare of members, are Sumber Sejahtera Credit Union Cooperative In South Kalimantan has a variety of profitable Deposit Products, Sumber Sejahtera Credit Union Cooperative In South Kalimantan has a variety of attractive Loan Products and low loan (interest) remuneration, Sumber Sejahtera Credit Union Cooperative In South Kalimantan has Deposit Protection Insurance and Insurance Loans, Family spirit of members of the Sumber Sejahtera Credit Union Cooperative in South Kalimantan has solidarity to help each other / solidarity of grief members and most importantly the Sumber Sejahtera Credit Union Cooperative can be trusted. Then the convenience for members is realized by the good service of all employees in serving members in all fields of cooperative business, in addition to the existence of the diverse Sumber Sejahtera Credit Union Cooperative aimed at improving the welfare of members, assuming that diverse business units will provide convenience for members in meeting their needs so that welfare will be achieved.